DEVELOPING ENCYCLOPEDIA OF MACROZOOBENTHIC INVERTEBRATES LEARNING MODULE TO IMPROVE STUDENTS’ LEARNING OUTCOME IN BIOLOGY SUBJECT - Rostikawati, R. Teti; Susanto, Lufty Hari; Rahayu, Eka Puspita (Universitas Tanjungpura, 2021)
This research is Research and Development (R&D) model used in the ADDIE model which was done on March until July 2019. The purpose of the study was to develop encyclopedia of macrozoobenthic invertebrates to improve student’s learning outcome. The research was conducted at a High School in Bogor, for the tenth grade students of MIPA 1 as the experimental class with the total number of 37 students and used one group pretest-posttest design. The instruments used in this study consist of expert validation sheets, multiple choice questions and questionnaire sheets to collect student responses about encyclopedia of learning module. Validation data shows that the feasibility test on the content of the material, language and presentations obtain values above 81% included the validity and appropriateness category for learning. The result of the questionnaire shows that a positive response was obtained with values above 82%. The average result obtained at pretest was 43,23 while the average result obtained at posttest was 79,90. The result of the N-Gain analysis shows a medium criterion of 0,6. In conclusion, the encyclopedia of macrozoobenthic invertebrates can improve student learning outcome.